Fiscal Policy Actions Ancillary to Growth: the Transition Economies - Kotosz, Balázs (Ekonomika, 2004)
The paper is looking for the reasons of the growth differences in transition economies. Empirical analyses justify that GDP growth is higher in countries where state reallocation is decreasing and where a tight fiscal policy has been kept. We can identify several budget restrictions that have expansionary effects, especially in the case of considerable cuts in budget deficits. These non-Keynesian results fit the earlier consequents of Alesina, Perotti and Giavazzi for OECD countries.